Questioning the Representation in Salman Rushdie’s The Satanic Verses - Adhikari , Rashmi Thapa (Patan Prospective Journal, 2025)
This paper examines Rushdie’s The Satanic Verses that shocked the world with the portrayal of the themes after its publication in 1988. This novel led to the loss of over twenty lives. It made its author go into hiding from the Ayatollah Khomeini's fatwa of 1989, where he remained under government protection ever since. The novel played a significant role in redefining the West's image of itself. The Iranian President Khamene'i justified his fatwa against Rushdie by similarly accusing him and "the world devourers" (the West) of publishing The Satanic Verses as a calculated move aimed at rooting out religion and religiousness, and above all, Islam and its clergy. The novel boldly explores religious identity, cultural hybridity, and the rivalry that ensues between tradition and modernity. The text depicts religious figures and themes that are aligned with Islam, the result of which is an issuance a Fatwa and several attempts on his life. The article analyzes the novel used by the ruler of Iran as a deliberate literary attempt to eradicate religion and religiousness, and more specifically, Islam and its clergy, in order to defend his fatwa against Rushdie. The objective of the paper is to demonstrate the conflict between tradition and modernity, religious identity, and cultural hybridity. The exploration of the study suggests that the novel portrays religious figures and themes that are consistent with Islam, which led to the issuance of a Fatwa and multiple attempts on his life. In his writings, Rushdie makes use of linguistic markers and literary devices to help define, mold, and differentiate his characters. Besides, it also helps to give a thorough and nearly immediate grasp of a character's past.